OSTEOMEATAL COMPLEX VARIATIONS IN CHRONIC RHINOSINUSITIS PATIENTS AT A TERTIARY CARE HOSPITAL: A RETROSPECTIVE STUDY - Jawad, Ayesha; Saira Iftikhar; Mumtaz Ahmad Umar; Farhan Ahmed; Maimoona Shafqat; Seema Naveed (Journal of Ayub Medical College Abbottabad, 2024)
Background: Rhinosinusitis is one of the most prevalent mucosal diseases of the sinuses globally. The definitive treatment for this condition is functional endoscopic sinus surgery (FESS). Computed tomography (CT) scans performed before and after surgery help visualize anatomical obstructions and confirm the success of the procedure. Rhinosinusitis presents with multiple anatomical variations in the osteomeatal complex. The objective of this study was to observe various anatomical variations in sinonasal diseases. Methods: A retrospective study was conducted with a sample size of 95 patients who underwent FESS over a four-year period, from January 2018 to May 2022. The study included patients diagnosed with sinonasal diseases, such as everted uncinate process, concha bullosa, paradoxical middle turbinate, deviated nasal septum, agger nasi, Onodi cells, and Haller cells. CT scans performed prior to surgery were analyzed. Data was processed using SPSS version 25. Results: The mean age of patients was 39.0 ± 14.0 years. The dominant age group was 20–30 years, accounting for approximately 32% of all patients. Among the 95 subjects, 68% were male and 32% female. The most common anatomical variation in the osteomeatal complex was a deviated nasal septum, observed in 43% of cases, followed by concha bullosa, reported in 27%. Conclusion: Preoperative CT findings provide valuable insights regarding the risk of chronic rhinosinusitis. The study identified a high prevalence of nasal septum deviation as a major anatomical obstruction in the reported cases, emphasizing its relevance in preoperative assessment.